Locutionary, Illocutionary, and Perlocutionary Speech Acts in the Comment Column of Instagram Account @jokowi - Haynun Natul Zuairiyah; Intan Sari Ramdhani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Every day humans interact as social beings to survive. Language is a communication tool in every human interaction. Currently communication is supported by many kinds of social media so that communication takes place quickly and can be done with anyone. One of the social media that is widely used in Indonesia is Instagram. Instagram is a social media used to upload and share photos and videos of its users. On every video and photo upload, users can add text which is usually called a caption and can provide feedback on an upload via comments. Through these two features speech occurs. Speech acts have three types, namely locutionary, illocutionary, and perlocutionary. This research uses descriptive qualitative method. The source of the data in this study was obtained from uploading greeting posters to the Instagram account @jokowi. Based on the research that has been done, 15 utterances were found in the three greeting poster uploads, namely, Mother's Day, Christmas, and New Year 2023 greeting posters. Based on the findings, the utterances most commonly found are illocutionary speech acts. This is due to the many comments that instruct the reader to follow something according to the story.